EKSEKUSI IKRAR TALAK MENURUT UNDANG-UNDANG NOMOR 50 TAHUN 2009 PERUBAHAN ATAS UNDANG-UNDANG NOMOR 7 TAHUN 1989 TENTANG PERADILAN AGAMA - Latifatul Fajriyah dan Abdul Rokhim (Universitas 17 Agustus 1945 Samarinda, 2020)
This study aims to find out why the decision on divorce application submitted by the husband is not final and how the role of Judges of the Religious Court in the execution of the divorce pledge. This type of research used in this study uses the Normative Juridical research method, namely by analyzing the articles in the legislation regarding the problem under study.The results of the research show that the final decision of a judge regarding divorce divorce is when all the procedures in filing for divorce divorce have been fulfilled legally. That is still in need of the pronunciation of divorce pledge made by the husband in front of the trial of the Religious Court. If the husband has pledged his divorce then the marriage is broken with all the legal consequences. In divorce divorce cases the judge's role is to guide the petitioner in pledging his divorce to the respondent, as well as witnessing the pronouncement of the divorce pledge.